47 Evaluating the impact of medical students in hospice teaching ward rounds. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Grewal, Bhajneek; Hill, Rosanna; Gillon, Suzie; Ward, Jason; Rayment, Clare
Abstract : Introduction: Healthcare professionals can be reluctant to invite medical students on ward rounds, especially in the context of emotive discussions. We present the results of a study analysing the impact of teaching ward rounds on patient experience in hospices. Methods: Eight hospices were invited to participate in this service evaluation. Six hospices across Yorkshire returned data. Inpatients were asked to complete an anonymous questionnaire after a teaching ward round, defined as consisting of a minimum of 3 members of staff, led by a senior doctor (consultant or specialty grade) and including at least one medical student. Results: Seventy-four questionnaires were returned. The vast majority (96%) of patients were happy for students to be present on the ward round. None of the patients who were in a shared bay at the hospice felt that this prevented them from asking questions. The presence of a relative was felt to be a positive factor during the ward round experience. Only 11% of patients felt that the presence of students negatively affected the discussion of sensitive issues. Conclusions: Our study shows that most patients had a positive response to the presence of medical students on ward rounds. Overall teaching ward rounds did not appear to negatively impact upon the discussion of sensitive topics. This study contains a small sample size and the results cannot be generalised across a palliative care population. Nonetheless it provides data in support of medical students participating in teaching ward rounds in hospices where sensitive discussions frequently take place.